Peran Orang Tua dalam Meningkatkan Membaca Al-Quran Anak Umur 7-12 Tahun Desa Sigala-Gala - Ismail Nasution; Silvera Ramadani Pasaribu; Lannita Hutabarat; Lisma Andriani Nasution; Ihsan Hasibuan; Ika Efni Oktapia Daulay (Kampus Akademik Publiser, 2025)
This study aims to determine the role of parents in improving the ability to read the Qur'an of children aged 7-12 years in Sigala-gala Village. The background of this study departs from the phenomenon that some children in the village still experience delays in reading the Qur'an even though they are elementary school age. The research subjects involved several parents, community leaders, and Quran teachers. The object of the research is the role of parents in providing motivation, exemplary, habituation, attention, and socio-economic support in supporting children to read the Qur'an. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing by checking the validity of the data using credibility, transferability, dependability, and confirmability. The results showed that the role of parents is very influential on children's ability to read the Qur'an. Parents who provide motivation, set an example, get used to reading the Qur'an at home, and provide adequate attention and learning facilities are able to encourage children to read the Qur'an more quickly and fluently. Socio-economic factors are also a significant support in the success of children's Qur'an education. This study is in line with the results of previous research in the last five years (2020-2025) which confirms that parental involvement is the main key in the success of children learning the Qur'an.